Application of Public Service Dominant Logic Through Value Cocreation in the Commercial Exchange Program - Mufaddhol, Agil; Marsasi, Endy Gunanto (Image : Jurnal Riset Manajemen, 2023)
This study examines a regional television broadcasting media company operating in Riau, Malay. This research was conducted to evaluate the problems in the company, especially the marketing used by the Riau Television company to provide facilities that support marketing in the Niaga Niaga Program. The research method is descriptive qualitative with primary and secondary data. This study used observation, interviews, and documentation as data collection methods. This study provides the results of an evaluation of the Bursa Niaga program from Riau Televisi, which creates shared value between broadcasters and users using the Public Service Dominant Logic or PDSL theory with the concept of Value Co-Creation implemented as an effort to develop marketing media from Riau Televisi. This research is expected to encourage Riau Television to degrowth the company, especially in marketing, which creates value on the social media that Riau Televisi uses.